Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing 2015
DOI: 10.18653/v1/d15-1203
|View full text |Cite
|
Sign up to set email alerts
|

Distant Supervision for Relation Extraction via Piecewise Convolutional Neural Networks

Abstract: Two problems arise when using distant supervision for relation extraction. First, in this method, an already existing knowledge base is heuristically aligned to texts, and the alignment results are treated as labeled data. However, the heuristic alignment can fail, resulting in wrong label problem. In addition, in previous approaches, statistical models have typically been applied to ad hoc features. The noise that originates from the feature extraction process can cause poor performance.In this paper, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
963
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,028 publications
(965 citation statements)
references
References 18 publications
2
963
0
Order By: Relevance
“…Mintz et al (2009) and Riedel et al (2010) have used manually engineered features based on part-of-speech tags and dependency parses to represent the target relations. Recently, Zeng et al (2015) and have shown that one can successfully apply convo-lutional neural networks to extract sentence-level features automatically.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mintz et al (2009) and Riedel et al (2010) have used manually engineered features based on part-of-speech tags and dependency parses to represent the target relations. Recently, Zeng et al (2015) and have shown that one can successfully apply convo-lutional neural networks to extract sentence-level features automatically.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the methods (Riedel et al, 2010;Zeng et al, 2015;Lin et al, 2016) focus on predicting a single relation type based on the combined evidence from all of the occurrences of an entity pair. Hoffmann et al (2011) and Surdeanu et al (2012) assign multiple relation types to each entity pair, such that the predictions are tied to particular occurrences of the entity pair.…”
Section: Related Workmentioning
confidence: 99%
“…We first introduce MIML and then describe the base neural network models we consider: 1 piecewise CNN (Zeng et al, 2015) (PCNN) and bidirectional GRU (Cho et al, 2014) (RNN). We also utilize the selective attention mechanism in for both PCNN and RNN models.…”
Section: Methodsmentioning
confidence: 99%
“…Residual learning is used to help the deep CNN network [12]. Zeng et al [13] split a sentence into three parts, and then applied max pooling to each part of the sentence over a CNN layer.…”
Section: Introductionmentioning
confidence: 99%